Boosting performance of inverted organic solar cells by using a planar coronene based electron-transporting layer. (September 2017) - Yu, Jiangsheng; Xi, Yuyin; Chueh, Chu-Chen; Xu, Jing-Qi; Zhong, Hongliang; Lin, Francis; Jo, Sae Byeok; Pozzo, Lilo D.; Tang, Weihua; Jen, Alex K.-Y.
Abstract: In this work, an alcohol-soluble, low-temperature processable and relatively thickness insensitive electron-transporting layer (ETL) comprising a planar coronene derivative, CDIN, was exploited to effectively enhance the photovoltaic performance of various inverted organic photovoltaics (OPVs). Besides the decent charge-transporting property, such CDIN ETL was manifested to facilitate the face-on orientation of atop bulk-heterojunction (BHJ) layers as evidenced by GIWAXS analysis, which might benefit from its discotic geometry endowed with strong face-on π–π stacking in solid-states and better compatibility to the constituent organic photoactive components. Consequently, an enhancement of over 9% in PCE can be achieved in the state-of-the-art fullerene-based OPVs to yield a PCE of 11.2% while over 13% enhancement can be realized in the representative non-fullerene OPVs to yield a PCE of 9%. Graphical abstract: An alcohol-soluble, low-temperature processable and relatively thickness-insensitive organic CDIN-based electron-transporting layer (ETL) has been exploited to effectively enhance the photovoltaic performance of various inverted organic photovoltaics (OPVs). Owing to its discotic geometry endowed with strong face-on π–π stacking in solid state and better compatibility to the constituent organic photoactive components, a high PCE of 11.17% can be achieved in the state-of-the-art fullerene-based OPVs. Highlights: An alcohol-soluble organic CDIN-based electron-transporting layer has been exploited in various inverted organic photovoltaics. Effective enhancements of the various photovoltaic performance can be achieved by using CDIN-based electron-transporting layer. A high PCE of 11.17% can be realized in the state-of-the-art fullerene-based organic photovoltaics.